On the sidelines of what works: scientifically based indifference - Wolgemuth, Jennifer R.; Marn, Travis M.; Sabnis, Sujay (International Journal of Research & Method in Education, 2021)
A team of systematic reviewers successfully completed a government-commissioned review of ‘what works to improve post-school outcomes for youth with disabilities’ in 2012. Despite its success, interviews with 10 review team members revealed dissatisfaction with the process and indifference to its outcomes. The purpose of our analysis was to examine how the systematic review process itself led to review team members’ feelings of indifference, resignation, and pessimism. Drawing on the writings of Henry Giroux, Gert Biesta, and Hanna Arendt that warn of the death of democracy and the rise of totalitarianism, we explored how the systematic review certification process, examinations, rules, and structures deadened democratic deliberation and critique necessary, we argue, to conducting good educational science. We end with a call for systematic reviews in education whose researchers, products, and processes remain ethically oriented to keeping democracy alive. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
2 citations (Crossref) [2023-10-31]
Keywords: dept.cur; peer-reviewed

Radical uncertainty is not enough: (In)Justice matters of post-qualitative research: - Wolgemuth, Jennifer R.; Marn, Travis M.; Barko, Tim; Weaver-Hightower, Marcus B. (International Review of Qualitative Research, 2021)
6 citations (Crossref) [2023-10-31]
Keywords: dept.cur; peer-reviewed